2020
DOI: 10.1038/s41598-020-59406-4
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Risk of Hepatitis B Virus Reactivation in HBsAg−/HBcAb+ Carriers Receiving Rituximab for Rheumatoid Arthritis

Abstract: to investigate the incidence and risk factors of hepatitis B virus (HBV) reactivation in HBV surface antigen (HBsAg) − / HBV core antibody (HBcAb) + patients who underwent rituximab (RtX) therapy for rheumatoid arthritis (RA). From January 2000 through December 2017, a total of 134 RA patients with various HBV serostatuses who received RTX at Dalin Tzu Chi Hospital were screened. Finally, 50 HBsAg − /HBcAb + patients were enrolled in this retrospective study. Baseline characteristics, comedications, and the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
4
37
0
1
Order By: Relevance
“…Rituximab appears to have the highest risk; one retrospective study showed that in 50 RA patients at risk for reactivation, four developed HBV reactivation, two of whom developed clinically significant hepatitis and one died as a result of their illness. 48 There does not seem to be a significant difference in risk of reactivation with nonrituximab biologics or methotrexate therapy. 49 Considering these risks of reactivations, the American Gastroenterology Association (AGA) and the American College of Rheumatology recommend routine screening for patients with RA treated with immunosuppressives.…”
Section: Hepatitis Bmentioning
confidence: 97%
“…Rituximab appears to have the highest risk; one retrospective study showed that in 50 RA patients at risk for reactivation, four developed HBV reactivation, two of whom developed clinically significant hepatitis and one died as a result of their illness. 48 There does not seem to be a significant difference in risk of reactivation with nonrituximab biologics or methotrexate therapy. 49 Considering these risks of reactivations, the American Gastroenterology Association (AGA) and the American College of Rheumatology recommend routine screening for patients with RA treated with immunosuppressives.…”
Section: Hepatitis Bmentioning
confidence: 97%
“…In the current cohort, the highest HBV reactivation rate (100%) was noted. HBV reactivation was determined by the HBV serologic status [ 7 , 37 , 38 ], host immune status, treatment duration, glucocorticoid comedication [ 17 ], and history of bDMARD use [ 5 , 39 ]. In the current study, all HBsAg+ patients underwent comedication with glucocorticoids and had a history of bDMARD use.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from Taiwan revealed that the incidence of HBV reactivation under rituximab treatment was up to 40% and 100% in HBsAg+ RA patients without or with steroid treatment [ 17 ]. Our previous report demonstrated that the incidence of HBV reactivation was up to 60% and 8% in HBsAg+ or HBsAg-/anti-HBc+ RA patients treated with rituximab [ 5 ]. According to the policy of National Health Insurance in Taiwan, RA patients with a poor response to rituximab should wait 6 months after the last dose of rituximab before switching to another biological agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In rheumatoid arthritis (RA), HBV can be reactivated by changes in the disease course and by drug use. [4][5][6][7] In ammatory arthritis patients receiving biologic disease-modifying antirheumatic drugs (bDMARDs) are thought to have a moderate risk (1-10%) of hepatitis B reactivation. 7 A previous study reports that without antiviral prophylaxis, HBV reactivation occurs in 62.5% of HBV carriers and 25% of patients with occult HBV infection undergoing treatment with tumor necrosis factor -alpha blockers.…”
Section: Introductionmentioning
confidence: 99%